Tantangan Mewujudkan Generasi Emas 2045 di Tengah Degradasi Karakter Akibat Globalisasi dalam Era Society 5.0 - Putri Sari Margaret Julianty Silaban; Arys Fadillah; Citra Irawan; Fadlin Pulungan (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Indonesia has a grand vision to realize the Golden Generation 2045, a generation excelling in intellect, skills, and character by the centennial celebration of its independence. However, globalization and technological advancements in the Society 5.0 era have triggered character degradation, posing a significant challenge. This study aims to analyze the main challenges, the impacts of character degradation, and formulate strategies to build a generation with strong character. A qualitative descriptive-analytical research method was employed, collecting primary data through observations, and secondary data from literature studies. The results indicate that key factors driving character degradation include the influence of foreign cultures, technology misuse, and individualism due to digitalization. The impacts manifest in declining religiosity, nationalism, and rising consumerism and hoaxes. Proposed strategies involve integrating Pancasila-based character education into curricula, optimizing the roles of families and communities, leveraging technology positively, and strengthening digital literacy and local cultural awareness. In conclusion, holistic efforts through collaboration among formal education, family environments, and national value-based policies are essential to nurture a globally competitive generation while preserving cultural identity.